Higher Education Productivity Measurement - Davood Hosseinpour (Islamic Azad University, Tabriz Branch, 2021)
The purpose of this applied descriptive survey was to measure the productivity of higher education. The research population consisted of first level different university faculty members and assistants from whom a cluster sample of 34 participants from Allameh Tabataba'I University, Tehran University and Sharif Industrial universities were randomly selected to partake in the study. The research data were collected employing a researcher-made productivity measurement questionnaire comprising four factors tapping quality, value added, efficiency and effectiveness. Smart-PLS software was employed to confirm the validity and reliability of the questionnaire and the structural and general fitting of the proposed model. The research data were analyzed via SPSS software and dependent samples t-test to answer the research questions. The findings demonstrated that overall productivity of higher education was below expectations and that higher education productivity facets including quality, value added, efficiency and effectiveness were far below favoured averages. The findings accentuate consistent measurement, causal scrutiny and planning as prerequisites for productivity enhancement of higher education.